2021
DOI: 10.1016/j.idm.2021.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Long, thin transmission chains of Severe Acute Respiratory Syndrome Coronavirus 2 may go undetected for several weeks at low to moderate reproduction numbers: Implications for containment and elimination strategy

Abstract: Severe Acute Respiratory Syndrome Coronavirus 1 (SARS-CoV-1) infections almost always caused overt symptoms, so effective case and contact management enabled its effective eradication within months. However, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) usually causes only mild symptoms, so transmission chains may grow to include several individuals before at least one index case becomes ill enough to self-report for diagnosis and care. Here, simple mathematical models were developed to evaluate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Today, many countries have the legal authority to impose quarantine which, in accordance with Article 3 of the International Health Regulations (2005), must be fully respectful of the dignity, human rights and fundamental freedoms of persons [ 15 ]. While contact tracing and quarantine are considered critical activities to reduce transmission [ 2 , 16 ], the effectiveness of contact tracing depends on many factors including compliance [ 17 , 18 ]. A rapid evidence review conducted early in the COVID 19 pandemic identified fourteen studies which assessed compliance to quarantine during earlier infectious disease outbreaks including mumps, Severe Acute Respiratory Syndrome (SARS) and Ebola.…”
Section: Introductionmentioning
confidence: 99%
“…Today, many countries have the legal authority to impose quarantine which, in accordance with Article 3 of the International Health Regulations (2005), must be fully respectful of the dignity, human rights and fundamental freedoms of persons [ 15 ]. While contact tracing and quarantine are considered critical activities to reduce transmission [ 2 , 16 ], the effectiveness of contact tracing depends on many factors including compliance [ 17 , 18 ]. A rapid evidence review conducted early in the COVID 19 pandemic identified fourteen studies which assessed compliance to quarantine during earlier infectious disease outbreaks including mumps, Severe Acute Respiratory Syndrome (SARS) and Ebola.…”
Section: Introductionmentioning
confidence: 99%
“…While contact tracing and quarantine are considered critical activities to reduce transmission [2,16], the effectiveness of contact tracing depends on many factors including compliance [17,18]. A rapid evidence review conducted early in the COVID 19 pandemic identified fourteen studies which assessed compliance to quarantine during earlier infectious disease outbreaks including mumps, Severe Acute Respiratory Syndrome (SARS) and Ebola.…”
Section: Introductionmentioning
confidence: 99%